Natural photosensitizer extraction from Delonix regia flowers for future photosensor for DSSCs applications - Niyamat I. Beedri; Habib M. Pathan; Sunita Salunke-Gawali (Next Energy)
This study explores the utilization of Delonix regia (DR) (Gulmohar flower) as a natural photosensitizer in the fabrication of self-powered photosensors via dye-sensitized solar cells (DSSCs). Various photoanodes, including ZnO, ZnO/TiO2, and ZnO/TiO2/Nb2O5, were investigated for their performance enhancement in DR-based photosensors. The photoanodes were fabricated using different deposition methods sensitized with DR photosensitizer and characterized through X-ray diffraction analysis, Field emission scanning electron microscopy (FE-SEM), UV–visible, Fluorescence spectroscopy, and Fourier transform infrared spectroscopy (FTIR) analysis. The absorbance spectrum results indicate improved photosensitizer adsorption in visible light for the ZnO/TiO2/Nb2O5/DR photoanode compared to other configurations. The scanning electron microscopy (SEM) cross-section image of ZnO/TiO2/Nb2O5 confirmed the formation of a multilayer photoanode. Chronoamperometry experiments were conducted to evaluate the photo sensing behavior, focusing on sensitivity, photoresponsivity, specific detectivity, and quantum efficiency within the solar spectrum range. Among the devices, ZnO/TiO2/Nb2O5 exhibited the highest photoresponsivity (1.2 × 10 −3 A/W) and photodetectivity (26.78 × 104 Jones), demonstrating promising advancements in DR-sensitized photosensors. This research highlights the exceptional performance of DR-sensitized photoanodes, particularly ZnO/TiO2/Nb2O5, in advancing the capabilities of photo-sensing devices. The investigated configuration exhibited a rapid response speed of 723 ms and a remarkable sensitivity of 89.87% in detecting photo signals. These findings emphasize the potential of DR photosensitizers to enhance photo-sensing activities, with significant implications for diverse applications in photodetection. By leveraging the unique properties of DR, particularly its incorporation into ZnO/TiO2/Nb2O5, this study underscores the promising prospects for developing efficient self-powered photosensors. The insights gleaned from this work pave the way for further exploration and optimization in organic photosensors.